Binocular integration and stereopsis in children with television torticollis - Yang, Cheng (BMC Ophthalmol, 2021)
BACKGROUND: To observe the characteristics of binocular integration and stereopsis in children with television torticollis. METHODS: A retrospective study was carried out, where data were collected from 25 children with television torticollis as the disease group after refractive error correction and 25 normal children as the control group. A virtual reality system was used to assess and analyze the characteristics of binocular integration by a contrast balance test and binocular stereopsis. RESULTS: The 25 children in the disease group included 17 males and 8 females with an average age of 7.5 ± 1.9 years old and an average binocular spherical equivalent of − 0.35 ± 1.46D. The 25 children in the control group were also 17 males and 8 females with an average age of 7.3 ± 2.2 years old and the average binocular spherical equivalent of − 0.48 ± 0.93D. No significant differences were found in the horizontal bar contrast balance test between the 2 groups at near and far distances. Near-distance vertical bar contrast balance test was normal in 23 subjects and suppressed in 2 subjects in the control group, while it was normal in 13 subjects and suppressed in 12 subjects in the disease group, which showed a statistically significant difference (P = 0.002). Far distance vertical bar contrast balance test was normal in 24 subjects and suppressed in 1 subject in the control group, normal in 7 subjects and suppressed in 18 subjects in the disease group, showing a statistically significant difference (P = 0.000). All subjects in the 2 groups showed 100〞 as near distance stereoacuity. At far distance, the mean stereoacuity was 176.00〞 ± 92.56〞 in the control group, and 352.00〞 ± 270.99〞 in the disease group, with a statistically significant difference (P = 0.011). CONCLUSION: By using virtual reality technology, defects in binocular visual function were found in children whose television torticollis persisted after regular refractive error correction. Television torticollis may be associated with the deficit of binocular integration for vertical bars and far distance stereopsis.